Ελεγχόμενη παραγωγή εντροπίας και η εφαρμογή της σε συστήματα μηχανών ή/και μηχανολογικών υλικών - Πολυβίου, Ιωάννης (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The activation of a spontaneous process between two fixed states compels a thermodynamic closed system to produce entropy with a magnitude that depends on the degree of spontaneity of the process. For the production of entropy to be utilized controllably for exploitation purposes it will have to be quantified or parametrized. For this to happen it will have to be understood through the sequential interpretation of all those fundamental concepts which comprise its physical understanding or its theoretical background. In the framework of this work after all the concepts and practical examples that are required so as to fully provide the physical interpretation of the production of entropy are fully spelled out and analysed in depth both in the macroscopic and microscopic level, the realization of parametrization and quantification for selective applications are carried out through the requisite equations of state as these arise based on the First and Second law of Thermodynamics.
Keywords: Thermodynamic closed system; Physical interpretation; Entropy; First law of Thermodynamics; Second law of Thermodynamics; Εντροπία; Θερμοδυναμικό κλειστό σύστημα; Πρώτο Νόμο της Θερμοδυναμικής; Δεύτερο Νόμο της Θερμοδυναμικής; Φυσική ερμηνεία